PENGARUH PERASAN KULIT JERUK NIPIS TERHADAP DAYA HAMBAT BAKTERI STREPTOCOCCUS MUTANS - Irmanita Wiradona; Suwarsono ,; Novi Anna Zakiyatul (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2014)
ABSTRACT The caries disease dental and oral health problems are high in Indonesia. The cause of caries disease one of which is the bacterium Streptococcus mutans. Efforts to prevent one of them with natural ingredients that lime peel. In lime peel essential oils are substances that are useful as antibacterial and phenols contained in the essential oil can denature bacterial cell proteins. The objective of this the effect of lime juice on the skin inhibition of Streptococcus mutans bacteria.This is a quasi experimental study (quasi-experimental). Research subjects bacterium Streptococcus mutans. The study was conducted using a concentration of 10%, 20%, 40%, and 80% respectively - each concentration done 3x treatment. The data was analyzed with parametric test using ANOVA followed by Post Hoc test.The results showed a large area of inhibition of the average juice lime peel with a 10% concentration of 7.73 mm, a 20% concentration of 9.13 mm, a 40% concentration of 10.54 mm, and the concentration of 80% by 14.23 mm. Anova analysis showed a significant (p 0.05) indicates that there is an influence juice lime peel in inhibiting the growth of Streptococcus mutans.The higher of the concentration, the greater the inhibition of the bacterium Streptococcus mutans. Key words : Leather Lime Juice, Streptococcus mutans